Geotechnical engineering design of a tunnel support system - a case study of Karuma (600MW) hydropower project - Ongodia, Joan Evelyn (Geotechnical Engineering Research Group, 2017)
Tunnels have been built since 2180 B.C., through the stone age. They became popular worldwide since the eighteenth century, as transportation, military, mining, conveyance, storage and flood control structures. Due to the increasing world population, urbanization and industrialization, the construction of underground tunnel structures are preferred as they limit interferences with existing surface uses of the land and water bodies. Although underground tunnels are a common flexible construction alternative, they are high hazard risk structures. The risks are mostly related to ground conditions. Tunnels buried at depth disturb in-situ conditions, cause ground instability and ultimately failure. Widespread tunnel failures, though not publicly advertised because of their adverse implications, have claimed human lives, cleared cities, cost 100 million United States dollars' worth in financial losses and year-long project delays. As such, stability of the structures is crucial to prevent the catastrophes thereby reducing societal outcries. Permanency of underground structures is ensured by provision of adequate resistance to any impeding failure of the ground surrounding deep underground excavations. The effectiveness of the ground-support interaction depends on geology, material properties, geotechnical parameters, loads of the surrounding ground mass and mechanism of the interaction. Using actual project information, the factors influencing stability, structural resistance as well as methods to select the required support are explored in this dissertation. The study used typical geological data of an underground tunnel component of Karuma, a proposed 600MW hydropower project in Uganda. It doubles as the largest hydropower project and first underground construction, to date. The project is located along the River Nile in a sensitive ecosystem neighboring both a major national park and the Great Rift Valley system in East Africa. The instability problem at Karuma was assessed using scientific and universal tunneling practice. Typical site data formed input for the geotechnical engineering design of the tunnel support based on analytical, observational and empirical methods. The study demonstrated that all methods were independent and dissimilar for the same geotechnical engineering challenge of the underground structure. The most comprehensive method was the one based on geotechnical engineering principles and rock mechanics theory. The outcomes of the different approaches in this study were unique functions of their underlying scientific philosophies. The study proposes that in designing adequate support systems to resist forces causing failure of underground tunnels, excavations buried in the ground should encompass several methods. The most conservative design should be chosen to ensure permanency.